Effectiveness of collaboration between oncology pharmacists and anaesthesiologists for inpatient cancer pain management: A pilot study in Taiwan. Issue 11 (November 2021) - Chen, Kuan-Ju; Tai, Yu-Ting; Chang, Elizabeth H; Kuo, Li-Na; Kuo, Chun-Nan
Objective: To evaluate the effectiveness of the collaboration between oncology pharmacists and anaesthesiologists for improving pain control management in cancer patients. Methods: This retrospective case–control pilot study enrolled inpatients with active cancer and a pain score of >3 at least once per day for 3 consecutive days. The study group was selected from June 2018 to January 2019. Patients with the same inclusion criteria were selected between November 2017 and May 2018 to serve as the comparison group. The primary outcome was the percentage of patients that experienced pain relief within 7 days from initial pain attack. Results: A total of 71 and 77 patients were enrolled in the study and comparison groups. More patients in the study group experienced pain relief within 7 days from the index date (78.9% [56 of 71 patients] versus 72.7% [56 of 77 patients], respectively). The service increased the rate of intervention from attending physicians within 4 days from index date and quality of opioid management. Conclusion: The collaboration between oncology pharmacists and anaesthesiologists for cancer pain management may be associated with an increase in the rate of pain relief in cancer patients with poor pain control.